Neuregulin-1 effects in metabolic changes induced by pulmonary arterial hypertension - Pinto, Ana Rita Barbosa (2018)
Pulmonary arterial hypertension (PAH) is a chronic rare disease, characterized by increased pulmonary vascular resistance (PVR) with progressive overload and remodelling of the right ventricle (RV), that eventually leads to right ventricular heart failure (RVHF). These derangements arise from a metabolic switch from glucose oxidation towards glycolysis, the Warburg effect, affecting glucose metabolism at the systemic level. The neuregulin-1 (NRG1), a protein that has been shown to play beneficial effects on PAH and RV hypertrophy, has also been associated with the regulation of glucose metabolism given its role in modulating the expression of glucose transporters (GLUTs). In this study we aimed to evaluate the effect of rhNRG1 chronic treatment on glycolysis pathway genes expression in the RV and skeletal muscle in a monocrotaline (MCT)-induced PAH animal model and in chronic hypoxia/Sugen5416 model that also reproduces key pathophysiological features from human PAH. We have found that RV GLUT1 and GLUT4 mRNA expression is altered in PAH and was similar between the MCT and hypoxia/Sugen5416 animal models, being this related with the development of RV hypertrophy (RVH). However, the treatment with rhNRG1 only attenuated GLUTs expression toward normal values in MCT-induced PAH model. The expression of GLUT1 and GLUT4 is correlated with cardiac markers of disease, while the glycolytic pathway genes are correlated with the morphophysiological changes resulting from the development of PAH in MCT model. From the analysis of some glycolytic pathway genes, we conclude that beyond GLUTs, several genes are related, not only with the Warburg effect, but also with the disease progression. We also found that the treatment with rhNRG1 attenuated the changes in some glycolytic pathway genes, resulting in an improvement of glucose metabolism. The glucose tolerance evaluation revealed that the animals with PAH from both models are insulin resistant and that the treatment with rhNRG1 regulated systemic glucose concentration in both animal models. In conclusion, the therapeutic effects of NRG1 in experimental PAH may be due, in part, to the regulation of metabolic changes associated with PAH progression and RV dysfunction, which were reflected in the reversion of the ventricular phenotype of the disease.